Theorizing about faith and faithfulness with Jonathan Kvanvig - McKaughan, Daniel J. (Religious studies, 2022)
What are faith and faithfulness, and how are they related? We consider two views that express very different answers to these questions. On our view, faith and faithfulness are distinct and yet complement each other. Faith is resilient reliance and faithfulness is resilient reliability, both of which involve conative and/or affective elements. In contrast, while Jonathan Kvanvig also holds that faith involves conative and/or affective elements, he identifies faith with a disposition to act in service of an ideal in the face of difficulty. However, this view of faith leads to some puzzling claims about how faith relates to faithfulness. We evaluate several claims suggested by what Kvanvig says, arguing both that his view loses sight of the distinctness of faith and faithfulness and that the inferences he wants to draw from faithfulness or faithful behaviour to faith are unjustified. Instead, we aim to show how the insights he calls to our attention can be better accommodated and explained by a more comprehensive, unified theory of faith and faithfulness and their relations.